Forward to Southeast Asia : Taiwan's economic and security alternatives. - Mo, Kuang Hwa. (2008)
This thesis will focus on the development of regional economic integration in Southeast Asia, and Taiwan's responsibility and effort to participate in this regional economic development (and Taiwan's role in it).